Eco-spiritual tourism as alternative tourism in Taro Village: Opportunity and challenge - L.K. Herindiyah Kartika Yuni; I Wayan Arta Artana (Journal of Applied Sciences in Travel and Hospitality, 2021)
This study aims to analyze the opportunities and challenges faced by Taro Village in developing eco-spiritual tourism. The data in this study were collected through observation, interviews with key informants determined based on purposive sampling and documentation. The data were analyzed using qualitative descriptive analysis to obtain a complete picture of the opportunities and challenges faced by Taro Village as a village that develops eco-spiritual tourism. There are various opportunities that have been empowered such as high visits to several objects, support from the government and local communities as religious communities who uphold the sacred value of nature, and the attention of educational institutions realized through training to improve human resources. However, Taro Village still faces various challenges in its development such as the community does not have the same understanding of the vision of the Eco-spiritual village, community involvement has not been maximized because the majority of the community are farmers and consider tourism as a side job, weather with quite high rainfall often hampers tourist activities, which are mostly conducted in the open space, such as activities in traditional villages, in particular "metekap", "melukat", and firefly attractions. From these opportunities and challenges, it can be suggested that Taro Village should identify and evaluate opportunities and challenges on a regular basis, determine the target market with certain demographic characteristics, learning from competitors to improve product quality to compete, Preserving the quality of nature and the readiness of human resources in sustainable tourism in Taro Village.